2-2=1/3(5p-9)
2-2 is 0. Easy. Okay, now, we do distributive property: (1/3*5p)+(1/3*-9)
We turn the 5p into 5/1p Now we multiply easier: 1/3*5/1p. 1*5 is 5 and 3*1 is 3, so our answer here is 5/3. It is in simplest form. Now, u do the same for 1/3*-9. 1/3*-9/1. 1*-9 is -9 and 3*1 is 3= -9/3. This can be simplified into -3.
Now we got 0=5/3p-3.
Add 3 to both sides to undo the subtraction. 0+3 is 3. and -3+3 cancels out. So now we got 3=5/3p. Now to undo the division we multiply 3/5.
3*3/5 is 9/5 and 5/3p*3/5 cancels out.
So our answer would be p=9/5